2014
DOI: 10.1128/jvi.03048-13
|View full text |Cite|
|
Sign up to set email alerts
|

Antigenic Properties of the HIV Envelope on Virions in Solution

Abstract: The structural flexibility found in human immunodeficiency virus (HIV) envelope glycoproteins creates a complex relationship between antigenicity and sensitivity to antiviral antibodies. The study of this issue in the context of viral particles is particularly problematic as conventional virus capture approaches can perturb antigenicity profiles. Here, we employed a unique analytical system based on fluorescence correlation spectroscopy (FCS), which measures antibody-virion binding with all reactants continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 96 publications
9
68
2
Order By: Relevance
“…These studies indicate that this epitope region remains buried at the interface of virion-associated HIV-1 trimers triggered with soluble CD4, despite the exposure of the coreceptor binding site. This is consistent with previous findings regarding exposure of the MAb A32 epitope on virions in solution and using a cell-cell fusion system (56,57,59) and points to an additional energy component likely provided by a conformational change in the d3d4 region of cell surface CD4, which is required for trimer unfolding during viral entry.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These studies indicate that this epitope region remains buried at the interface of virion-associated HIV-1 trimers triggered with soluble CD4, despite the exposure of the coreceptor binding site. This is consistent with previous findings regarding exposure of the MAb A32 epitope on virions in solution and using a cell-cell fusion system (56,57,59) and points to an additional energy component likely provided by a conformational change in the d3d4 region of cell surface CD4, which is required for trimer unfolding during viral entry.…”
Section: Discussionsupporting
confidence: 80%
“…Since soluble CD4 does not expose the A32 subregion (Fig. 5C) (56), and since we know that it is exposed during cell-to-cell fusion and during viral entry (57), either binding to cell surface CD4 or binding of trimer-CD4 complexes to coreceptor exposes this region. We tested this hypothesis by spinoculating AT-2 inactivated HIV-1 BaL virions onto the surfaces of CEM-Nkr and CEM-Nkr-CCR5 ϩ cells and testing binding of MAbs N5-i5 and 2.2c.…”
Section: Resultsmentioning
confidence: 99%
“…1C and D). Our results are in agreement with previous reports indicating that the highly conserved region recognized by anti-cluster A antibodies is buried inside the Env trimer, where it is not readily accessible for binding in the ligand-free closed state (10,(21)(22)(23)(24)(25)(26)(27). Accordingly, anti-cluster A and HIV ϩ sera recognized more efficiently cells infected with a virus lacking Nef and Vpu and hence exposing Env at higher levels and in its CD4-bound conformation (2,5,28).…”
supporting
confidence: 92%
“…In the case of HIV-1 infection, both nAbs and non-nAbs against Env (gp160 or gp120 plus gp41) are simultaneously elicited, and the levels of these Abs rise in response to the gradual increase in viral load and are maintained at high levels throughout the infection (7,8). Although anti-HIV-1 nAbs have been extensively studied in vitro and in vivo, non-nAbs have received little attention (44,53). Studies have demonstrated that almost all HIV-1-infected individuals develop Abs capable of neutralizing autologous viruses (16).…”
Section: Discussionmentioning
confidence: 99%